Modulation of cyclobutane thymine photodimer formation in T(11)-tracts in rotationally phased nucleosome core particles and DNA minicircles - Wang, Kesai (Nucleic Acids Res, 2017)
Cyclobutane pyrimidine dimers (CPDs) are DNA photoproducts linked to skin cancer, whose mutagenicity depends in part on their frequency of formation and deamination. Nucleosomes modulate CPD formation, favoring outside facing sites and disfavoring inward facing sites. A similar pattern of CPD formation in protein-free DNA loops suggests that DNA bending causes the modulation in nucleosomes. To systematically study the cause and effect of nucleosome structure on CPD formation and deamination, we have developed a circular permutation synthesis strategy for positioning a target sequence at different superhelix locations (SHLs) across a nucleosome in which the DNA has been rotationally phased with respect to the histone octamer by TG motifs. We have used this system to show that the nucleosome dramatically modulates CPD formation in a T(11)-tract that covers one full turn of the nucleosome helix at seven different SHLs, and that the position of maximum CPD formation at all locations is shifted to the 5΄-side of that found in mixed-sequence nucleosomes. We also show that an 80-mer minicircle DNA using the same TG-motifs faithfully reproduces the CPD pattern in the nucleosome, indicating that it is a good model for protein-free rotationally phased bent DNA of the same curvature as in a nucleosome, and that bending is modulating CPD formation.